Bioenergetic disruption of human micro-vascular endothelial cells by antipsychotics - Elmorsy, Ekramy; Smith, Paul A. (Elsevier, 2015)
Antipsychotics (APs) are widely used medications, however these are not without side effects such as disruption of blood brain barrier function (BBB). To investigate this further we have studied the chronic effects of the typical APs, chlorpromazine (CPZ) and haloperidol (HAL) and the atypical APs, risperidone (RIS) and clozapine (CLZ), on the bioenergetics of human micro-vascular endothelial cells (HBVECs) of the BBB. Alamar blue (AB) and ATP assays showed that these APs impair bioenergenesis in HBVECs in a concentration and time dependent manner. However since these effects were incomplete they suggest a population of cell bioenergetically heterogeneous, an idea supported by the bistable nature by which APs affected the mitochondrial transmembrane potential. CPZ, HAL and CLZ inhibited the activity of mitochondrial complexes I and III. Our data demonstrates that at therapeutic concentrations, APs can impair the bioenergetic status of HBVECs, an action that help explains the adverse side effects of these drugs when used clinically.